The importance of formative assessment based on students’ perception - Arinaa Sabilah Ghozali; Peptia Asrining Tyas (Jurnal Konseling dan Pendidikan, 2022)
EFL (English for Foreign Language) refers to the teaching and learning of English in educational settings where the society does not use English as their first language. Most EFL teachers in Indonesian formal schools developed their formative assessment according to their own perception, whereas several studies had proven that formative assessment should be designed based on students’ perception. The aim of this study is to describe the students’ perception of formative assessment practices in EFL class, which use the formative assessment cycle as the conceptual model. The research design in this study is survey design. The subject of this study is 11th grader students in State High School 8, Malang, Indonesia. The study is held throughout the English subject in the odd semester of 2022/2023 school year. The data analysis techniques used is descriptive quantitative. The quantitative data distribution of five dimensions of formative assessment shows that all of the subject percept every indicator positively. The results confirm that designing a formative assessment based on students’ perception is highly needed, where along the process, teachers could reflect their quality of teaching, and in the same time, students are facilitated to improve their goals, reducing material-misconception, expanding understanding in strength and weakness, and also developing better students-teacher communication in learning.